2014
DOI: 10.1016/j.oraloncology.2013.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Vanilloids induce oral cancer apoptosis independent of TRPV1

Abstract: SUMMARY Objective To investigate the mechanisms of vanilloid cytotoxicity and anti-tumor effects in oral squamous cell carcinoma (OSCC). Materials and methods Immunohistochemistry and qPCR analyses demonstrated expression of the TRP vanilloid type 1 (TRPV1) receptor in OSCC. Using cell proliferation assays, calcium imaging, and three mouse xenograft models, prototypical vanilloid agonist (capsaicin) and antagonist (capsazepine) were evaluated for cytotoxic and anti-tumor effects in OSCC. Results OSCC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 36 publications
(42 reference statements)
5
82
0
Order By: Relevance
“…In order to examine whether the observed cytotoxicity was due to the generation of ROS and subsequent apoptosis, it was used flow cytometry and co-treatment with the antioxidant N-acetyl-cysteine (NAC). The two analyses confirmed the hypothesis, namely the apoptosis was produced by ROS induction [39].…”
Section: Activation Of Trpv1 By Capsaicinsupporting
confidence: 73%
See 1 more Smart Citation
“…In order to examine whether the observed cytotoxicity was due to the generation of ROS and subsequent apoptosis, it was used flow cytometry and co-treatment with the antioxidant N-acetyl-cysteine (NAC). The two analyses confirmed the hypothesis, namely the apoptosis was produced by ROS induction [39].…”
Section: Activation Of Trpv1 By Capsaicinsupporting
confidence: 73%
“…The consequence of this attenuation of the Ca2+ efflux mechanism is the elevation in ([Ca2+]i and promotion of cell death pathways modulated by Ca2+, such as those of the mitochondria [35]. These observations explain the apoptotic response overexpression of TRPV1 after capsaicin activation lung [36], glioma [37], urothelial [38]and KB cells (epidermal carcinoma) [39,40].TRPV1 was functionally implicated in these events as they were markedly inhibited by the TRPV1 antagonist, the capsazepine. However, Gonzales et al, investigated the mechanisms of vanilloid cytotoxicity and its anti-tumor effects in oral squamous cell carcinoma (OSCC) and showed that OSCC cell lines treated with capsaicin had significantly reduced cell viability, but pre-treatment with capsazepine failed to reverse these effects.…”
Section: Activation Of Trpv1 By Capsaicinmentioning
confidence: 99%
“…Oxidative stress may generate reactive oxygen species (ROS) in tumor cells, which may increase the cytotoxic activity of therapeutic drugs [44]. Though curcumin acts as a free radical scavenger, an effect on ROS generation has been reported in many cancer types [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to see whether a topical cream containing capsaicin or RTX can eliminate actinic keratosis. Of note, capsaicin appears to kill oral SQCC cells in culture independent of TRPV1 (Gonzales et al, 2014).…”
Section: G Transient Receptor Potential Channels In Cancermentioning
confidence: 96%